2021
DOI: 10.3390/jcm10214866
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolic Syndrome with Sensorineural Hearing Loss

Abstract: The prevalence of sensorineural hearing loss has increased along with increases in life expectancy and exposure to noisy environments. Metabolic syndrome (MetS) is a cluster of co-occurring conditions that increase the risk of heart disease, stroke and type 2 diabetes, along with other conditions that affect the blood vessels. Components of MetS include insulin resistance, body weight, lipid concentration, blood pressure, and blood glucose concentration, as well as other features of insulin resistance such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Although there are no reports on risk factors associated with an increase in hearing thresholds on the healthy side of patients with ISSNHL, the primary risk factors are those related to aging. There are a number of reported risk factors for age-related hearing loss, including advancing age, being male, smoking, alcohol use, DM, HTN, heart disease, noise exposure, and genetic predisposition 7,[14][15][16][17][18]20,21,46 . In the present study, older ages, being male, and vascular disease were associated with higher PTA thresholds on the healthy side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are no reports on risk factors associated with an increase in hearing thresholds on the healthy side of patients with ISSNHL, the primary risk factors are those related to aging. There are a number of reported risk factors for age-related hearing loss, including advancing age, being male, smoking, alcohol use, DM, HTN, heart disease, noise exposure, and genetic predisposition 7,[14][15][16][17][18]20,21,46 . In the present study, older ages, being male, and vascular disease were associated with higher PTA thresholds on the healthy side.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused our study on audiograms of the healthy side in patients with ISSNHL. The pattern of the audiogram of the patient’s healthy side may reflect normal changes related not only to aging 6 , but also to a variety of medical conditions and factors related to a patient’s background, such as whether the patient has atherosclerosis and is subject to certain genetic factors 7 , 8 . Therefore, we hypothesized that the audiogram on the healthy side of patients with ISSNHL could be a useful additional measure to aid in the diagnosis and prognosis of ISSNHL, which is currently not done.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative influence of metabolic syndrome (MetS) on hearing relates to the number of diagnostic components met Rim et al (2021) designed a study to explore the relationship between MetS and sensorineural hearing loss in Korea. The results showed that MetS subjects had higher mean puretone hearing thresholds than subjects without MetS in all age groups (P < 0.001); moreover, among MetS subjects, there was a significant association between the number of MetS diagnostic components met and the hearing loss rate (P < 0.0001).…”
Section: Hypertension Aggravates the Development Of Age-related Heari...mentioning
confidence: 99%
“…In this regard, an increase in the risk of several alterations has been reported, including decreased muscle strength and sarcopenia, frailty, cognitive deficits, sleep disturbances, multiple chemical sensitivity, sensorineural hearing loss, kidney stone disease, etc. [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%